ASIAN POLITICAL NEWS FRAMING: A SYSTEMATIC LITERATURE REVIEW - Pradana, Nawfal Oktavialdi; Rahyadi, Irmawan; Sarnoto, Natan Ekaputera (INFOKUM, 2022)
News framing has a different meaning for every scholar but the outline of every definition is that news framing helps individuals to understand reality, this reality can be shaped by any kind of information. In this case, the news or mass media is the tool to understand reality. This journal explains to you the recent update on news framing topics with around 40 journals from various publishers being reviewed to discover the trend and the characteristics of news framing topics. The finding from the research is that most of the news framing topic journals used qualitative methodology, moreover, the relation with politics is also one of the strong characteristics of this topic. Another finding from the research is that there is a lot of Asian content related to this topic, the journal being reviewed shows us there is strong popularity in the Asia continent. Even so, there are still many affiliated journals from other countries, but indeed the Asian continent is the biggest contributor. In addition, all the journals from the Asian continent were found to have a lot of political content, so it can be concluded that there are many journals from Asia that also discuss politics.